Dendritic cell co-stimulatory and co-inhibitory markers in chronic HCV: An Egyptian study - Fouad, Hanan (Baishideng Publishing Group Co., Limited, 2013)
AIM: To assess co-stimulatory and co-inhibitory markers of dendritic cells (DCs) in hepatitis C virus (HCV) infected subjects with and without uremia. METHODS: Three subject groups were included in the study: group 1 involved 50 control subjects, group 2 involved 50 patients with chronic HCV infection and group 3 involved 50 HCV uremic subjects undergoing hemodialysis. CD83, CD86 and CD40 as co-stimulatory markers and PD-L1 as a co-inhibitory marker were assessed in peripheral blood mononuclear cells by real-time polymerase chain reaction. Interleukin-10 (IL-10) and hyaluronic acid (HA) levels were also assessed. All findings were correlated with disease activity, viral load and fibrogenesis. RESULTS: There was a significant decrease in co-stimulatory markers; CD83, CD86 and CD40 in groups 2 and 3 vs the control group. Co-stimulatory markers were significantly higher in group 3 vs group 2. There was a significant elevation in PD-L1 in both HCV groups vs the control group. PD-L1 was significantly lower in group 3 vs group 2. There was a significant elevation in IL-10 and HA levels in groups 2 and 3, where IL-10 was higher in group 3 and HA was lower in group 3 vs group 2. HA level was significantly correlated with disease activity and fibrosis grade in group 2. IL-10 was significantly correlated with fibrosis grade in group 2. There were significant negative correlations between co-stimulatory markers and viral load in groups 2 and 3, except CD83 in dialysis patients. There was a significant positive correlation between PD-L1 and viral load in both HCV groups. CONCLUSION: A significant decrease in DC co-stimulatory markers and a significant increase in a DC co-inhibitory marker were observed in HCV subjects and to a lesser extent in dialysis patients.